Evaluating quality of implementation in physical activity interventions based on theories of motivation: current challenges and future directions. Issue 1 (1st January 2017) - Quested, Eleanor; Ntoumanis, Nikos; Thøgersen-Ntoumani, Cecilie; Hagger, Martin S.; Hancox, Jennie E.
ABSTRACT: The evidence base pointing towards the maladaptive health consequences of an inactive lifestyle highlights the need for interventions that are effective in changing and maintaining physical activity behaviours. Theories of motivation are frequently applied to inform the content and delivery of such interventions. Systematic monitoring and evaluation of the quality of intervention implementation is therefore an important step in understanding if and how theories of motivation can be adopted and effectively applied to promote and/or sustain physical activity behaviours. However, intervention implementation quality in studies that aim to apply motivation theory to promote physical activity is often under-reported. The purpose of this article is, first, to review contemporary approaches used to monitor and evaluate intervention implementation; we outline the degree to which these methods have been used effectively in research concerned with applying theories of motivation to impact physical activity behaviours. Second, we identify and discuss specific challenges in effectively measuring quality of implementation faced by researchers who adopt a motivation theory basis to their work. Finally, recommendations for methods to monitor and evaluate intervention implementation in future trials aiming to promote physical activity based on theories of motivation are also proposed.